Motif Batik Tegal: Pengaruh Mataram, Pesisiran dan Islam - Siti Maziyah (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
BATIK – motif is one of the cultural results that can show the identity of the region and has a unique cultural background. This article highlights the issue of Tegal Batik motif. What kind of batik Tegal is ? What cultures are behind the Tegal batik motifs? I apply the research method with historical approach to find the history of Tegal. Who are the actors in carrying out cultural changes in Tegal, especially related to the emergence of batik motifs. Based on the history, it will be known why Tegal batik has such motives. The results showed that based on the history of Tegal, batik motifs get influence from some other cultural areas besides the Tegal community itself, namely from the Kingdom of Mataram and from the Pasisiran region. In addition, batik motifs Tegal also get a strong influence from “wong kaji”, namely the Muslim traders that taft with the Islam included in describing to the batik motifs. Again, there is one type of batik produced by rural communities of Tegal, called “folk-batik”.